2017
DOI: 10.1002/adfm.201701138
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic‐Tuned Flash Cu Nanowelding with Ultrafast Photochemical‐Reducing and Interlocking on Flexible Plastics

Abstract: Herein, a high‐performance copper nanowire (Cu NW) network (sheet resistance ≈ 17 Ω sq−1, transmittance 88%) fabricated by plasmonic‐tuned flash welding (PFW) with ultrafast interlocking and photochemical reducing is reported, which greatly enhance the mechanical and chemical stability of Cu NWs. Xenon flash spectrum is tuned in an optimized distribution (maximized light intensity at 600 nm wavelength) through modulation of electron kinetic energy in the lamp by generating drift potential for preferential phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 43 publications
0
65
0
Order By: Relevance
“…Nevertheless, the tungsten halogen lamp–induced welding employs specific illuminating setup and nitrogen atmosphere, which complicates mass production of AgNW films . Using a xenon flash lamp as a light source requires a sophisticated flash lamp system, and may need to accurately modulate the discharge voltage and pulse duration of flash ignition to optimize welding condition . The feature of the laser with a focused spot beam significantly hinders its application in the large‐scale fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the tungsten halogen lamp–induced welding employs specific illuminating setup and nitrogen atmosphere, which complicates mass production of AgNW films . Using a xenon flash lamp as a light source requires a sophisticated flash lamp system, and may need to accurately modulate the discharge voltage and pulse duration of flash ignition to optimize welding condition . The feature of the laser with a focused spot beam significantly hinders its application in the large‐scale fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…This enhanced photothermal characteristic of the AgNW–N66 blends is attributed to the efficient coupling of the laser with the plasmon modes. Previously, Ko and coworkers demonstrated that plasmonic heating (i.e., by a continuous wave laser and flash lamp) in Cu and Ag NWs could lead to the melting of a polymer substrate and welding at the NW junctions. They also showed that plasmonic heating in a single NW was maximized when the polarization of the excitation was aligned with the transverse modes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of research groups have demonstrated flexible memories, thin film transistors (TFTs), and integrated circuits (ICs) as key technology for data processing, information storage, and communication . Since Kim et al reported functional flexible resistive random access memory (RRAM), various chalcogenide‐based phase change memories (PCMs) as well as RRAMs using inorganic (e.g., WO 3 , Al 2 O 3 , HfO 2 , TiO 2 ), carbon (graphene, carbon nanotubes (CNTs)), and organic materials have been fabricated on polymer films. In addition, an ultrathin TFT and Si‐based large‐scale integration (LSI) were demonstrated for high‐density flexible electronics .…”
Section: Introductionmentioning
confidence: 99%